Extreme rainfall in Scotland on 11 and 12 August 2020: evaluation of impact‐based rainfall forecasts. (28th April 2021) - Sharpe, Michael; Cranston, Michael
Abstract : On 11 and 12 August 2020 some of the highest rainfall depths in recent memory were observed across a wide area of Scotland, causing significant impacts. As part of its operational partnership with the Scottish Environment Protection Agency, the Met Office provides a bespoke, probabilistic, impact‐based Heavy Rainfall Alert Service. This system successfully forecast 58 of the 60 severe‐impact events that were identified by post‐processed radar.